Incidence and morbidity of craniocervical arterial dissections in atraumatic subarachnoid hemorrhage patients who underwent aneurysmal repair. (8th August 2014) - Carr, Kevin; Rincon, Fred; Maltenfort, Mitchell; Birnbaum, Lee; Dengler, Bradley; Rodriguez, Michelle; Seifi, Ali
Abstract : Background: No studies have assessed the incidence of craniocervical arterial dissections (CCADs) and its association to mortality in hospitalized patients with a primary diagnosis of atraumatic subarachnoid hemorrhage (SAH) requiring aneurysmal repair. We hypothesize that the incidence of CCADs in these patients has increased over time as well as its association to mortality. Methods: We conducted a 9 year retrospective assessment of the incidence of CCADs in patients hospitalized with a primary diagnosis of an SAH requiring repair and the effect of CCAD on mortality. Using the Nationwide Inpatient Sample (NIS), we queried records from 2003 to 2011 for an ICD-9 (International Classification of Diseases-9) code corresponding to admissions for atraumatic SAH. Demographical data, incidence of CCADs, type of aneurysmal repair, length of hospital stay, and hospital mortality were recorded. Multivariate logistical regression models were fitted to assess for the impact of CCAD on inhospital mortality and morbidity. Results: During the period 2003–2011, of the NIS reported 18 260 patients who required aneurysmal SAH repair, 9737 (53.32%) underwent endovascular coiling and 8523 (46.48%) had surgical clipping. There were 131 patients in the cohort with reported CCADs: 94 (71.75%) of these patients had received endovascular coiling repair and 37 (28.25%) had undergone surgical clipping repair. Patients who underwent endovascular coiling had a higher rate of CCADs in this cohort (OR 2.94; 95% CI 2.00 to 4.31, p<0.0001). The incidence of CCADs in this population increased by an average rate of 9.4% per year (OR 1.14; 95% CI 1.06 to 1.23, p<0.0006), from 0.49% in 2003 to 1.10% in 2011. The diagnosis of CCAD added 3 and 6 more days to median length of hospitalization stay for surgical clipping and endovascular coiling, respectively. The unadjusted rate of mortality was 8.4% in the CCADs subgroup, and the presence of CCAD was not a predictor of mortality in our multivariate regression model (OR 0.68; 95% CI 0.36 to 1.27, p=0.2244). Conclusions: Our study indicates an annual increase in the incidence of CCADs in patients admitted with SAH who require aneurysmal repair. More than two-thirds of these patients that developed CCADs had undergone endovascular coiling repair. A diagnosis of CCAD increased the length of hospital stay but had no statistically significant association with mortality in this patient population.